China and the international human rights regime, 1982-2017 / Rana Siu Inboden. - Inboden, Rana Siu, 1973- (Cambridge University Press, 2021)
Rana Siu Inboden examines China's role in the international human rights regime between 1982 and 2017 and, through this lens, explores China's rising position in the world. Focusing on three major case studies - the drafting and adoption of the Convention against Torture and the Optional Protocol to the Convention against Torture, the establishment of the UN Human Rights Council, and the International Labour Organization's Conference Committee on the Application of Standards - Inboden shows China's subtle yet persistent efforts to constrain the international human rights regime. Based on a range of documentary and archival research, as well as extensive interview data, Inboden provides fresh insights into the motivations and influences driving China's conduct and explores China's rising position as a global power.